Distribution, Interaction and Functional Profiles of Epiphytic Bacterial Communities from the Rocky Intertidal Seaweeds, South Africa - Selvarajan, Ramganesh (Sci Rep, 2019)
Interrelations between epiphytic bacteria and macroalgae are multifaceted and complicated, though little is known about the community structure, interaction and functions of those epiphytic bacteria. This study comprehensively characterized the epiphytic bacterial communities associated with eight different common seaweeds collected from a rocky intertidal zone on the Indian Ocean at Cape Vidal, South Africa. High-throughput sequencing analyses indicated that seaweed-associated bacterial communities were dominated by the phyla Proteobacteria, Bacteroidetes, Firmicutes, Cyanobacteria, Planctomycetes, Actinobacteria and Verrucomicrobia. Energy-dispersive X-ray (EDX) analysis showed the presence of elemental composition in the surface of examined seaweeds, in varying concentrations. Cluster analysis showed that bacterial communities of brown seaweeds (SW2 and SW4) were closely resembled those of green seaweeds (SW1) and red seaweeds (SW7) while those of brown seaweeds formed a separate branch. Predicted functional capabilities of epiphytic bacteria using PICRUSt analysis revealed abundance of genes related to metabolic and biosynthetic activities. Further important identified functional interactions included genes for bacterial chemotaxis, which could be responsible for the observed association and network of elemental-microbes interaction. The study concludes that the diversity of epiphytic bacteria on seaweed surfaces is greatly influenced by algal organic exudates as well as elemental deposits on their surfaces, which triggers chemotaxis responses from epiphytic bacteria with the requisite genes to metabolise those substrates.